4d transition-metal doped hematite for enhancing photoelectrochemical activity: theoretical prediction and experimental confirmation. Issue 25 (21st March 2015) - Pan, Haijun; Meng, Xiangying; Cai, Jiajia; Li, Song; Qin, Gaowu
<x xml:space="preserve">Abstract</x> To explore the photoelectrochemical efficiency of hematite as a photoanode, we comprehensively investigate the electronic structures of hematite doped with 4d transition-metal X (X = Y, Zr, Mo, Tc, Rh, and Ru) based on the density-functional theory (DFT).